Lupus mesenteric vasculitis disguised as urticaria with abdominal pain: a case report with 10 months follow-up observation - Huang, Chaoyuan; Mo, Jiahao; Ye, Zhenhao (Frontiers in Immunology, 2025)
Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease characterized by multi-system involvement, with gastrointestinal manifestations often presenting diagnostic challenges due to their non-specificity. Mesenteric vasculitis, a rare but severe complication of SLE, carries a high misdiagnosis rate and mortality if it cannot be identified promptly. We report a case of a 27-year-old female with SLE presenting initially with atypical abdominal pain and duodenal edema. Due to her history of urticaria, she was initially mistaken for urticaria related abdominal pain. After a correct diagnosis, there was still progress despite conventional glucocorticoid therapy. The patient achieved remission following high-dose methylprednisolone pulse therapy, with sustained stability over 10 months of follow-up. This highlights a focus on long-term efficacy with extended follow-up, which is less common in similar past reports. This case highlights the importance of early recognition of SLE-related mesenteric vasculitis, particularly in patients with non-specific gastrointestinal symptoms, and emphasizes the necessity of aggressive immunosuppressive therapy to improve prognosis.